(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2026)
Persicaria decipiens is a traditional medicinal plant to treat skin conditions such as ringworm and bites from snakes, dogs and insects used by the people of Nagaland, India. The study investigates and compares the phytoconstituents compounds and antibacterial activity of Persicaria decipiens fresh and dry leaves extracts. Fresh and dry leaves of Persicaria decipiens were extracted using hexane and methanol in a Soxhlet apparatus. The extracts were investigated to phytochemical screening using standard procedures. The antibacterial efficacy of the extracts at various concentrations 50 mg, 100 mg, 150 mg, 200 mg, 250 mg and 300 mg were tested against Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus and Bacillus subtilis using agar well diffusion method. DMSO were used as negative control and ampicillin at 2 mcg were used as standard positive control respectively. The fresh leaf methanol and hexane extracts were more effective than dry leaves methanol and hexane extracts against the test bacteria. The antibacterial activity of fresh leaf methanol extract was observed at 300 mg concentration with 21±1 mm inhibition zone against Klebsiella pneumoniae, while for the dry leaf methanol extracts was observed at 300 mg concentration with zone of inhibition 7.67±0.57 mm against Bacillus subtilis. The fresh hexane extracts were observed at 200 mg with zone of inhibition of 16.66±0.57 mm against Bacillus subtilis while for the dry leaf hexane extracts was observed at 300 mg with 10±1 mm zone of inhibition against Klebsiella pneumoniae. Phytochemical screening of the extracts results that both fresh and dried leaf methanol extracts contained alkaloids, tannins, saponins, phenols and flavonoids. Also, it is observed that the fresh leaf hexane extracts confirmed the presence of steroids while the dried leaf hexane extract was tested positive for tannins. These studies provide information about Persicaria decipiens that contain excellent phytochemical compounds and fresh and dry leaf extracts can be used as antibacterial agent.